2007
DOI: 10.2105/ajph.2006.094813
|View full text |Cite
|
Sign up to set email alerts
|

Improving Disclosure and Consent

Abstract: The recent flood of research concerning pollutants in personal environmental and biological samples-blood, urine, breastmilk, household dust and air, umbilical cord blood, and other media-raises questions about whether and how to report results to individual study participants. Clinical medicine provides an expert-driven framework, whereas community-based participatory research emphasizes participants' right to know and the potential to inform action even when health effects are uncertain. Activist efforts off… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
99
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 109 publications
(104 citation statements)
references
References 16 publications
3
99
0
Order By: Relevance
“…Communicating individual results when there is a lack of health guidance values to interpret the data may empower individuals or could cause worry and concern (Brody et al, 2007). Washburn's experience from interviewing HBM study participants suggested that frustration due to an individual's limited ability to take action to protect themselves from future exposures is also an issue (Washburn, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…Communicating individual results when there is a lack of health guidance values to interpret the data may empower individuals or could cause worry and concern (Brody et al, 2007). Washburn's experience from interviewing HBM study participants suggested that frustration due to an individual's limited ability to take action to protect themselves from future exposures is also an issue (Washburn, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…justice, equity, and truth) into risk analysis by involving the affected public in assessing risk and designing risk communication methods (NRC 1996a; Cox 2013). This is similar to the four guidelines to protecting human research participants and deciding whether to report individual results outlined in Brody et al (2007) and Fernandez et al (2003): autonomy (right to know), beneficence (maximum good), nonmalfeasance (minimize harm), and justice (distribution of benefits and harm). A cultural model of risk communication makes use of local knowledge in risk studies and recognizes the relevant experience of the local community (Cox 2006; Corburn 2005; Dewey 1954).…”
Section: 0 Participatory Approachesmentioning
confidence: 82%
“…Communicating the findings and the potential risks associated with the findings is a crucial and integral step in the ERT process. Community members need to learn the results of exposure studies and the potential associated risks regardless of their educational background (Brody et al 2007; Morello-Frosch et al 2009; Adams et al 2011). .…”
Section: 0 Environmental Research Translationmentioning
confidence: 99%
“…Furthermore, social media became an important avenue by which the research team was contacted to conduct interviews with local media (eg local newspapers, radio). Social media has previously been identified as a means of increasing the impact and the accessibility of research for participants, including participants living in Indigenous communities [32,33]. …”
Section: Communicationmentioning
confidence: 99%